EFFECTS OF SYMPATHOMIMETIC AGENTS ON ELECTROCARDIOGRAM INDEXES IN PATIENTS WITH BRONCHIAL ASTHMA - I. G. Fomina; G. K. Makchnach; D. A. Zateyschikova; A. I. Tarzimanova (Столичная издательская компания, 2015)
Aim. To study effects of sympathomimetic agents on electrocardiogram (ECG) indexes in patients with bronchial asthma (BA) in exacerbation stage complicated by respiratory insufficiency and sympathomimetic agents overdose. Material and methods. 40 patients with persistent BA of various severities with respiratory insufficiency and sympathomimetic agents overdose were investigated. ECG was performed and P wave, QRS, duration and dispersion of corrected QT interval (QTc) were analyzed. Results. Mean QTc dispersion correlated with asthma severity and was 76,8±5,9 ms1/2, 87,9±5,1 ms1/2, 87,8±3,1 ms1/2 in patients with mild, moderate and severe BA, respectively. Significant correlation between QTc dispersion and BA duration was found. QTc dispersion level was directly connected with duration of use of β-agonists and their overdose. Average QTc dispersion in patients who used more than 20 daily doses of inhaled β-agonists was 89,0±5,8 ms1/2. Conclusion. Increase in QTc dispersion directly depends on BA duration and severity. β-agonist overdose results in growth of QTc dispersion, which has arrhythmogenic potential.